2015
DOI: 10.1002/pola.27629
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizability of Exo‐methylene‐lactide toward vinyl addition and ring opening

Abstract: This work examines the stereochemical control and polymerizability of exo-methylene-lactide (MLA) or (6S)-3-methylene-6-methyl-1,4-dioxane-2,5-dione, a chiral monomer derived from L-lactide, toward vinyl-addition and ring-opening polymerization (ROP) pathways, respectively. Currently, no information on the stereochemistry of the vinyl-addition polymerization of MLA is known, and the possible ROP pathway is unexplored. Accordingly, this work first investigated the stereochemical control and other characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…ROP of 1 is also unproductive (Supporting Information Table S2 ), instead promoting monomer decomposition. In line with work by Miyake et al, we confirmed that 1 prefers regio‐selective alcoholysis rather than productive ring‐opening, with the benzyl alcohol initiator initially serving as the alcohol source. Addition of alternative alcohols generated a family of new small molecule products (Supporting Information Scheme S1 ).…”
Section: Resultssupporting
confidence: 91%
“…ROP of 1 is also unproductive (Supporting Information Table S2 ), instead promoting monomer decomposition. In line with work by Miyake et al, we confirmed that 1 prefers regio‐selective alcoholysis rather than productive ring‐opening, with the benzyl alcohol initiator initially serving as the alcohol source. Addition of alternative alcohols generated a family of new small molecule products (Supporting Information Scheme S1 ).…”
Section: Resultssupporting
confidence: 91%
“…Several recent reports have indicated that Zr, Zn, or Li enolates can initiate lactide polymerization. 1822 …”
mentioning
confidence: 99%
“…Chen and co‐workers also studied briefly the free‐radical vinyl polymerization of MLA, obtaining materials with properties similar to those reported ( M n = 180 kg mol −1 , T g ranging from 229 to 254 °C). [ 448 ] Copolymers with γ‐MMBL and dimethylene lactide were also prepared. Their attempts to perform the direct ROP of MLA were however unsuccessful, as the conjugated double bond is probably too reactive toward the catalysts used for this reaction.…”
Section: Polymerization Of (Meth)acrylic Monomers and Analogsmentioning
confidence: 99%